Rural youth: Determinants of migration throughout the world - de Brauw, Alan (International Fund for Agricultural Development, 2019)
The decision of whether to migrate or not is one of many potentially important decisions that young men and women make throughout the developing world. This study takes a unique look at the determinants of youth migration across seven different countries using recently collected data, indirectly testing both broad and specific hypotheses related to migration. A major finding is that individual characteristics are more important determinants of migration than household characteristics. Furthermore, there is little evidence that credit constraints or relative deprivation are correlated with migration at a nationally representative level, holding other things constant.